Analisis Perancangan Sistem Monitoring untuk Perangkat Portable Smart Fish Feeder Berbasis Website - Rofi'i, Ahmad Rofi'i (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2025)
The purpose of this research is to analyze the design of a website-based interface that supports a monitoring and scheduling system for portable smart fish feeders. Portable smart fish feeders are a technological innovation designed for the fish feeding process. This device consists of various components, some of which are ESP32 as a microcontroller, an ultrasonic sensor as a detector of feed availability on the device, a pH sensor as a reader of the acidity or alkalinity of pond water, and a stepper motor as a regulator of the opening of the feeding plate. From these components, several value data will be taken to be managed and stored in real-time in firebase and displayed on the interface website as monitoring information. The results of the analysis produce a website-based interface as a monitoring medium and feed scheduling to support the use of portable smart fish feeders that can be accessed through various devices, thereby increasing user flexibility. Based on the data analysis, a percentage of >50% was obtained which, when converted to descriptively based on the assessment scale, can be concluded that the software quality of the functionality suitability characteristics is acceptable and appropriate. The final calculation analysis obtained a percentage of 90% in the usability test. The score indicates that the software quality from the usability characteristics is appropriate and when interpreted with a Likert scale is included in the very good category. The success rate during this stage of testing was 98%, where according to Telcordia standards if the percentage result obtained ≥ 95% can be declared passed so that this website has met the reliability characteristics. Based on the results of the performance efficiency test in this study, it can be concluded that the feed monitoring and scheduling website created has met the performance efficiency characteristics.